Quasi-phase-matched third harmonic generation in organic multilayers. Issue 1 (December 2018) - Kim, Jiung; Kumar, CH.; Cha, Myoungsik; Choi, Heejoo; Kim, Kyung-Jo; Peyghambarian, N.
Abstract We report the first realization of quasi-phase-matched (QPM) third harmonic generation in isotropic polymer films. Spin-coated thin films of ethyl-violet molecules dispersed in a polymer host (EV) were used as cubic nonlinear optical media because of their transparency at both the fundamental (1230 nm) and the third harmonic (410 nm) wavelengths. A passive layer of a UV-curable material was formed to compensate the phase shift between the two light waves after propagating through each EV layer. We fabricated a series of samples with 1 4 EV layers (0 3 alternatingly coated passive layers). The third harmonic output power showed a quadratic increase with the number of layers, providing a strong evidence for successful quasi-phase-matching. A conversion efficiency of 0.15% was observed with a 190 fs pulse input.